2023
DOI: 10.1002/advs.202205752
|View full text |Cite
|
Sign up to set email alerts
|

3D In Vitro Blood‐Brain‐Barrier Model for Investigating Barrier Insults

Abstract: Blood-brain-barrier (BBB) disruption has been associated with a variety of central-nervous-system diseases. In vitro BBB models enable to investigate how the barrier reacts to external injury events, commonly referred to as insults. Here, a human-cell-based BBB platform with integrated, transparent electrodes to monitor barrier tightness in real time at high resolution is presented. The BBB model includes human cerebral endothelial cells and primary pericytes and astrocytes in a 3D arrangement within a pump-fr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 90 publications
0
16
0
Order By: Relevance
“…39 Where possible, imaging techniques like phase-contrast or fluorescent microscopy, should also be employed for the continuous monitoring of the growth of the cells on the culture surface, and for the validation of the proper, confluent brain endothelial cell layer in the biochip, 4,40 A new BBB-on-chip model by Wei et al integrated barrier monitoring by TEER measurement and fluorescence microscopy in real time. 41 On the other hand, the monitoring of chemical and biochemical signals can be accomplished at separate locations, with connections to the primary BBB module through microfluidic channels. 29,42 It is anticipated, therefore, that we will soon see the creation of modular networks consisting of microfluidic BBB chip and biosensor systems, which will have a wide range of applications in both fundamental, scientific research and practical use.…”
Section: Problems and Perspectivesmentioning
confidence: 99%
See 3 more Smart Citations
“…39 Where possible, imaging techniques like phase-contrast or fluorescent microscopy, should also be employed for the continuous monitoring of the growth of the cells on the culture surface, and for the validation of the proper, confluent brain endothelial cell layer in the biochip, 4,40 A new BBB-on-chip model by Wei et al integrated barrier monitoring by TEER measurement and fluorescence microscopy in real time. 41 On the other hand, the monitoring of chemical and biochemical signals can be accomplished at separate locations, with connections to the primary BBB module through microfluidic channels. 29,42 It is anticipated, therefore, that we will soon see the creation of modular networks consisting of microfluidic BBB chip and biosensor systems, which will have a wide range of applications in both fundamental, scientific research and practical use.…”
Section: Problems and Perspectivesmentioning
confidence: 99%
“…5. 4,24,41,101 Reports on whether shear stress increases paracellular tightness at the BBB are somewhat conflicting. In one of the first papers describing a BBB-on-chip device, Booth and Kim found that TEER was elevated by more than 10-fold in response to shear stress (dyn cm −2 not specified).…”
Section: The Effect Of Shear Stress On Bbb Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…[52,225] Barrier models like the BBB can guide the generation of standardized data from MPS equipped with sensors like TEER around the barrier. [226,227] Researchers can collaboratively develop and share assay methods, incorporating real-time/functional data collection from P-MPS and integrating sensors within the device. [66,228] Third, adopting AI-driven processing for swift and reliable data generation is crucial, as previously discussed.…”
Section: Clinical Translation Of P-mpsmentioning
confidence: 99%